Performance comparison of the artificial neural network and the k-nearest nieghbor classifiers in classroom speech intelligibility prediction application - Mohd Ridhwan Tamjis; M. Naufal Mansor; Paulraj, Murugesa Pandiyan, Assoc. Prof.; A. Nazri Abdullah; Raymond B. W. Heng; Sazali Yaacob, Prof. Dr. (Science Academy, 2011)
Link to publisher's homepage at http://sciacademypublisher.com